BMI-based nutritional assessment of children aged 11–17 years in rural Ellisras, Limpopo province - Themba T. Sigudu; Thandiwe N. Mkhatshwa; Kotsedi D. Monyeki (Journal of Public Health in Africa)
Background: Childhood malnutrition, including both undernutrition and overnutrition, remains a significant public health concern in many low- and middle-income countries, including South Africa. Understanding the anthropometric characteristics and obesity predictors among rural South African adolescents is crucial for informing targeted public health interventions.